Muscle injury rates in professional football increase with fixture congestion: an 11-year follow-up of the UEFA Champions League injury study - Bengtsson, H.; Ekstrand, J.; Hägglund, M. (British Journal of Sports Medicine, 2013)
Background: The influence of fixture congestion on injury rates and team performance has only been scarcely investigated.